2018
DOI: 10.5114/fn.2018.74660
|View full text |Cite
|
Sign up to set email alerts
|

Interactive involvement of hippocampal cAMP/PKA and cyclooxygenase-2 signaling pathways in spatial learning in the Morris water maze

Abstract: Introduction: Accumulated evidence shows that the cAMP-PKA signaling pathway plays a key role in memory functions. Cyclooxygenase-2, a critical player in neuroinflammation, has been confirmed in the pathogenesis of neurodegenerative diseases. This study is aimed to assess the effect of the interaction of cAMP-PKA and cyclooxygenase pathways on spatial memory acquisition in animal models. Material and methods: In the present study, the effects of the four-day bilateral intra-hippocampal infusions of H-89 as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Inhibition of PKA signaling pathway causes learning and memory deficiency [11,12] and increase in apoptosis and autophagy [13]. Our previous studies in rats have also illustrated that intra-hippocampal infusion of H-89 impairs spatial memory formation in Morris water maze (MWM) task [14,15]. It has also been shown that post-training bilateral intrahippocampal (i.h.)…”
Section: Introductionmentioning
confidence: 98%
“…Inhibition of PKA signaling pathway causes learning and memory deficiency [11,12] and increase in apoptosis and autophagy [13]. Our previous studies in rats have also illustrated that intra-hippocampal infusion of H-89 impairs spatial memory formation in Morris water maze (MWM) task [14,15]. It has also been shown that post-training bilateral intrahippocampal (i.h.)…”
Section: Introductionmentioning
confidence: 98%
“…The equipment was supplied by Chengdu Taimeng Science and Technology Co., Ltd., China. The test was began on the 40th day after the first day of gavaging, including navigation test and probing test as other studies [11]. The day after MWM test finishing, rats were capitalized and brain tissues were obtained through perfusion sampling and fresh sampling.…”
Section: Methodsmentioning
confidence: 99%
“…The Morris water maze is the most frequently used device in behavioural neuroscience. The standard detection procedure has been described previously (Deng et al 2016;Tabrizian et al 2018). Briefly, the experiment was carried out in a round white pool (size, 94 cm in diameter and 31 cm deep), filled with water to a depth of 30 cm at a temperature of $25 C. A 25-cm 2 Plexiglas square was used as the escape platform and was placed in the centre of one quadrant in the pool, $15 cm from the pool's edge, and submerged 1 cm beneath the water surface.…”
Section: Morris Water Maze Testmentioning
confidence: 99%